ANALISIS REKONSILIASI FISKAL ATAS LAPORAN KEUANGAN KOMERSIAL PT.DEF BERDASARKAN UNDANG-UNDANG PPH NOMOR 36 TAHUN 2008 - Kurnia, Stephanie; Widjaja, Purnamawati Helen (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research was conducted with the aim of knowing the cause of the difference between profit by company (commercial profit) and profit according to tax (fiscal profit). In addition, this study was also conducted to determine the appropriate tax rates and calculations. Data obtained in the form of financial statements of PT. DEF, SPT (Annual Notification Letter), and interview results. The research method uses descriptive research and qualitative analysis methods. The results of this study indicate that there are differences in the recognition of vehicle usage costs, telephone costs, depreciation and amortization costs, entertainment costs, and interest income. The company is correct in applying tax rates and in accordance with applicable tax provisions.